Prediction of oxidative stability in bulk oils using dielectric constant changes. (1st May 2019) - Woo, YunSik; Kim, Mi-Ja; Lee, JaeHwan
Highlight: Effects of amphiphilic compounds on dielectric constant in bulk oils were determined. Monoacylglycerols (MAGs), lecithin, and moisture increased dielectric constant in corn oil. Free fatty acids like oleic and linoleic acids decreased dielectric constant. Oils with low oxidative stability had high dielectric constant in bulk oil. Dielectric constant showed high correlation with the percentage of unsaturated fatty acids in bulk oil. Abstract: The effects of amphiphilic compounds on the dielectric constant of bulk oils were determined and the utility of the dielectric constant as a reliable parameter for predicting the oxidative stability of edible oils was evaluated. As the content of monoacylglycerols (MAGs), lecithin, and moisture increased, the dielectric constant of modified corn oil increased at different rates, whereas the addition of free fatty acids, including oleic and linoleic acid, decreased the dielectric constant of modified corn oil. Unoxidized fresh bulk oils showed a wide range of dielectric constants, from 8 for canola oils to 33 for flaxseed oils. The dielectric constant showed a strong correlation with the percentage of unsaturated fatty acids in the bulk oils. Oils with low oxidative stability had a high dielectric constant. Overall, the dielectric constant of bulk oils is strongly correlated with the content of amphiphilic compounds, moisture content, and degree of unsaturation of fatty acids.